A case study on corrosion conditions and guidelines for repair of a reinforced concrete chimney in industrial environment. Issue 3 (25th November 2022) - Carsana, Maddalena; Gastaldi, Matteo; Redaelli, Elena
Abstract: This paper presents a case study of corrosion damage of a concrete chimney sited in a steel production plant in front of the Mediterranean Sea. The aggressive environment to which the chimney is exposed and its limited accessibility make the assessment of its condition critical. Destructive and non-destructive tests have been carried out over time to evaluate possible deterioration phenomena of concrete and corrosion of the reinforcement. The available documentation both on the construction and on previous repair interventions, besides the results of several investigations are discussed in the paper with the aim of assessing the chimney and proposing guidelines for the design of a durable and effective repair intervention, in relation with reinforcement corrosion. Results show that it is not possible to identify a single cause of damage, but rather a synergistic effect of corrosion of steel reinforcement due to chlorides ingress and carbonation and a moderate chemical attack of concrete due to exposure to fumes of the plant. Moreover, although the chimney was repaired several times, such interventions, not properly realized, promoted corrosion rather than control it.